State-permeated capitalism in large emerging economies - Nölke, Andreas 1963-; Ten Brink, Tobias 1976-; May, Christian 1976-; Claar, Simone 1983- (Routledge, 2020)
"This book systematically analyzes the economic dynamics of large emerging economies from an extended Comparative Capitalisms perspective. Coining the phrase 'state-permeated capitalism', the authors shift the focus of research from economic policy alone, towards the real world of corporate and state behaviour"--
Includes bibliographical references and index
Keywords: Öffentliches Unternehmen / (DE-627)091381169 / (DE-STW)11628-6; Kapitalismus / (DE-627)091370035 / (DE-STW)11046-0; Wirtschaftspolitik / (DE-627)091401143 / (DE-STW)10987-4; BRICS-Staaten / (DE-627)605992126 / (DE-STW)29740-1